Mobile phone app-based or face-to-face pulmonary rehabilitation in COVID-19 survivors - Vajihe Atashi; Marzieh Hashemi; Shila Haghighat; Raheleh Sadegh; Ramin Sami; Mobina Bahadori (Wolters Kluwer Medknow Publications, 2023)
Background: Pulmonary Rehabilitation (PR) is recommended as a standard, effective, and important treatment for COVID-19 survivors who remain symptomatic after the acute phase. Therefore, we aimed to compare the effect of mobile phone-based PR application with face-to-face PR on the quality of life, anxiety, depression, and daily life activities of COVID-19 survivors. Materials and Methods: A quasi-experimental was conducted on 65 COVID-19 survivors during 2022. Convenient sampling was done based on the inclusion criteria. The intervention group (n = 31) received PR through a mobile phone application, and the control group (n = 34) received face-to-face PR. Data were collected before and after the intervention in both groups using a demographic information questionnaire, SF-12, the hospital anxiety and depression scale, and Barthel scale. For all tests, a maximum error of 5% was considered. Results: The two studied groups had no statistically significant difference with respect to all the investigated variables at baseline (p > 0.05). After the intervention, the mean anxiety and depression score of the patients in the control group was significantly lower than the intervention group (t = −3.46, f = 63, p = 0.01). After our intervention, there was no statistically significant difference in the mean quality of life and daily life activity scores between the two groups (t = −0.68, f = 63, p > 0.05). Conclusions: The application of PR does not show a statistically significant difference in terms of improving the quality of life and daily activities compared with the face-to-face method; we suggest that the PR application be used as a cost-effective method when face-to-face PR is not possible.